Method for degrading polyethylene glycol terephthalate micro-plastic
Through electrolysis under specific conditions through electrochemical oxidation, the problems of low degradation efficiency and high cost of polyethylene terephthalate microplastics in the prior art are solved, and efficient and environmentally friendly microplastic degradation effect is achieved.
Patent Information
- Application Number
- CN202411595126.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art has problems such as high cost, harsh degradation reaction conditions, low degradation efficiency, and great pollution and harm to the environment when degrading polyethylene terephthalate microplastics.
Through electrochemical oxidation, the IrO2-Ta2O5/Ti electrode and graphite sheet electrode are electrolyzed under specific conditions to degrade PET microplastics. The method includes adding PET microplastic powder to an electrolyte containing surfactant, adjusting the pH to 4 to 7, stirring the electrolysis at 80°C to 90°C, controlling the current density to 5mA/cm2 to 20mA/cm2, and the electrolysis time is 2h to 12h.
It realizes rapid degradation of polyethylene terephthalate microplastics in a short time without adding a catalyst, with a degradation rate of 68%, strong adaptability, good environmental compatibility, easy to implement, and low cost.
Smart Images

Figure CN119661900A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material degradation, and in particular relates to a method for degrading polyethylene terephthalate microplastics. Background Art
[0002] Plastics may break during use and after disposal, producing particles with a diameter of less than 5 mm, which are called microplastics (MPs). Polyethylene terephthalate (PET) is a common packaging plastic with low manufacturing cost, usually single-use and low recycling rate. Although PET contains a high proportion of aromatic terephthalate units, the ester bonds on its main chain have extremely low hydrolysis; even long-term immersion in water at room temperature cannot change the physical and chemical properties of PET, and it is difficult to degrade under natural conditions, causing harm to the environment and human health. Therefore, artificial degradation methods are needed to remove MPs in the environment to reduce harm to the environment and human body.
[0003] Studies have shown that under the action of reactive oxygen species (ROS) induced by long-term ultraviolet radiation, MPs can undergo morphological changes and chemical chain breaks, thereby degrading. However, due to the low energy intensity of ultraviolet rays, the degradation time of most MPs is very long and the degradation efficiency is low. Photocatalytic systems can partially degrade plastics, but they will release volatile organic compounds. At the same time, it is difficult to recover the catalyst, which causes secondary pollution to a certain extent. Some studies use microbial bacteria isolated from wastewater, sludge and sediment to decompose MPs, but this method makes it take longer for microplastics to be significantly degraded. Electrochemical advanced oxidation process (EAOP) technology is an efficient organic pollutant degradation technology with the advantages of strong adaptability, good environmental compatibility and easy implementation. At present, important progress has been made in the degradation of soluble organic pollutants in water.
[0004] There are some authorized patents in the field of PET material degradation: a method for degrading polyethylene terephthalate (patent number: ZL200710175704.2), using ionic liquid to degrade polyethylene terephthalate; a method for degrading polyethylene terephthalate (patent number: 201110044490.1), using 1-butyl-3-ethylimidazolium bromide ionic liquid and methanol as solvents, polyethylene terephthalate undergoes alcoholysis reaction under the action of a catalyst, and ethylene glycol and dimethyl terephthalate are obtained after filtration and separation; a method for degrading polyethylene terephthalate (patent number: 201110044490.1) Patent No.: ZL201310638098.9), a magnetic ionic liquid is obtained by preparing HAp-γ-Fe2O3 and 1-methyl-3-(3-propyltriethoxysilane) imidazole chloride, and the magnetic ionic liquid is used as a catalyst to degrade PET in an aqueous phase system; there are also some patents that use catalysts to degrade polyethylene terephthalate: a method for catalytic alcoholysis of polyethylene terephthalate (patent number: ZL201110139360.6) and a method for catalytic degradation of polyethylene terephthalate using polymetallic oxygen clusters (patent number: 201410166733.2).
[0005] There are public literature reports on the use of supercritical methanol to degrade PET materials (Study on methanolytic depolymerization of PET with supercritical methanol for chemical recycling); the use of urea as an efficient and reusable catalyst for the glycolysis of polyethylene terephthalate (PET) waste (Urea as an efficient and reusable catalyst for the glycolysis ofpoly(ethylene terephthalate)wastes and the role of hydrogen bond in this process); the use of superparamagneticγ-Fe2O3 nanoparticles as a reusable catalyst for the alcoholysis of polyethylene terephthalate (PET) (Superparamagneticγ-Fe2O3 nanoparticles as an easily recoverable catalyst for the chemical recycling of PET); Deep eutectic solvents as highly active catalysts for the fast and mild glycolysis of polyethylene terephthalate (PET) poly(ethylene terephthalate)(PET)); First-Row Transition Metal-Containing Ionic Liquids as Highly Active Catalysts for the Glycolysis of Poly(ethylene terephthalate)(PET)
[0006] The methods adopted in the above patents and public documents have the problems of high cost, harsh degradation reaction conditions, low degradation efficiency, and great pollution and harm to the environment. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a method for degrading polyethylene terephthalate microplastics, which has simple reaction conditions, low cost and high degradation rate.
[0008] The purpose of the present invention can be achieved by the following technical solutions:
[0009] The present invention provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0010] S1, pre-treating polyethylene terephthalate to obtain PET microplastic powder;
[0011] S2, adding the PET microplastic powder obtained in step S1 to an electrolyte containing a surfactant, adjusting the pH of the electrolyte to 4-7, stirring and electrolyzing at a temperature of 80° C. to 90° C. to degrade the PET microplastic.
[0012] Furthermore, the specific steps of the pretreatment are: mixing polyethylene terephthalate and water in a mass ratio of 1:15 to 1:25, placing it in a hydrothermal reactor at 170°C to 190°C for 11h to 13h, then cooling it to 20°C to 30°C, filtering it and drying it to obtain PET microplastic powder.
[0013] Furthermore, the mass ratio of polyethylene terephthalate to water is 1:20, and after mixing, the mixture is placed in a hydrothermal reactor and maintained at 180°C.
[0014] Furthermore, the specific steps of electrolysis are: using an IrO2-Ta2O5 / Ti electrode as an anode and a graphite sheet electrode as a cathode, inserting the two electrodes used as a cathode and an anode respectively into an electrolyte, adding a surfactant and the PET microplastic powder obtained in step S1 to the electrolyte, and then stirring the electrolysis to degrade the PET microplastics. After the electrolysis is completed, the undegraded PET microplastics are filtered out using a 0.45 μm filter membrane and dried.
[0015] Furthermore, in step S2, aeration treatment is performed while stirring the electrolysis.
[0016] Furthermore, during the stirring electrolysis process in step S2, the current density is controlled at 5 mA / cm 2 ~20mA / cm 2 ; The electrolysis time is 2h~12h; The aeration flow rate is 0mL / min~100mL / min.
[0017] Furthermore, the electrolyte is a 0.01-0.1 mol / L Na2SO4 aqueous solution, preferably a 0.05 mol / L Na2SO4 aqueous solution.
[0018] Furthermore, the surfactant is selected from any one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, sodium dodecyl sulfonate, and sodium dodecylbenzene sulfonate, preferably sodium dodecyl sulfate (SDS).
[0019] Furthermore, the mass concentration of the surfactant is 0 mg / L to 100 mg / L.
[0020] Furthermore, the particle size of the PET microplastic powder is 145 mesh to 155 mesh, preferably 150 mesh.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The present invention provides a method for degrading polyethylene terephthalate microplastics, which degrades PET microplastics by electrochemical oxidation. As the temperature rises, the degradation efficiency increases accordingly. At 85°C, the degradation rate of PET microplastics reaches 68%; the optimal current density of electrolysis is 10mA / cm 2 , at this time, the weight loss rate reaches a maximum value. When the current density continues to increase, more bubbles appear on the electrode surface, which hinders the contact between MPs and the electrode surface, and at the same time, side reactions that are not conducive to the reaction will occur; pH will affect the concentration of conductive ions in the solution and thus affect the electron transfer rate of the solution. The optimal pH for degrading PET microplastics is 5. The degradation rate of PET microplastics is the highest under weakly acidic conditions. When the pH value is low, the active substances in the solution are consumed, thereby slowing down the reaction rate of MPs degradation. When the pH value is higher than the optimal condition, the redox potential of the active species decreases, reducing the degradation effect; adding surfactant SDS and aeration treatment promotes the electrolysis reaction, but changes in SDS concentration and aeration rate do not significantly improve the degradation efficiency. In summary, the optimal experimental conditions are electrolysis temperature: 85℃; current density: 10mA / cm 2 ; pH = 5; SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min. Under these conditions, the degradation weight loss of PET MPs can reach 68% after 6 hours of electrolysis.
[0023] (2) The present invention provides a method for degrading polyethylene terephthalate microplastics. Through electrochemical oxidation, polyethylene terephthalate microplastics can be quickly degraded in a short period of time without adding a catalyst. The method has strong adaptability, good environmental compatibility, and is easy to implement.
[0024] (3) The present invention provides a method for degrading polyethylene terephthalate microplastics. Compared with biodegradation, photodegradation and other conventional advanced oxidation technologies, the method of the present invention has the advantages of fast degradation speed, easy operation and low cost. After 6 hours of electrolysis, the degradation rate of PET MPs can reach 68%; after 10 hours of electrolysis, the degradation rate of PET MPs can reach 70%. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1Schematic diagram of the electrochemical degradation device of polyethylene terephthalate (PET) microplastics of the present invention, wherein 1 is an anode-iridium tantalum electrode, 2 is a cathode-graphite sheet electrode, and 3 is air;
[0026] Figure 2 These are scanning electron microscope photographs of polyethylene terephthalate (PET) microplastics before and after electrochemical degradation in Example 1 of the present invention, wherein (a) is a scanning electron microscope photograph before electrochemical degradation, and (b) is a scanning electron microscope photograph after electrochemical degradation;
[0027] Figure 3 It is the weight loss rate of the polyethylene terephthalate (PET) microplastics at different times of electrochemical degradation in Example 1 and Examples 14-18 of the present invention. DETAILED DESCRIPTION
[0028] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0029] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0030] The present invention provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0031] S1, pretreatment: polyethylene terephthalate and water are mixed in a mass ratio of 1:15 to 1:25, placed in a polytetrafluoroethylene hydrothermal reactor at 170°C to 190°C for 11h to 13h, then cooled to 20°C to 30°C, filtered and dried to obtain PET microplastic powder. Further, preferably as follows: polyethylene terephthalate and water are mixed in a mass ratio of 1:20, placed in a polytetrafluoroethylene hydrothermal reactor at 180°C for 12h, then cooled to 25°C, filtered and dried to obtain PET microplastic powder.
[0032] S2, degradation of PET microplastics: Figure 1 As shown, Figure 1The schematic diagram of the electrochemical degradation device of polyethylene terephthalate (PET) microplastics of the present invention is shown in FIG. 1, wherein 1 is an anode-iridium tantalum electrode, 2 is a cathode-graphite sheet electrode, and 3 is air. The IrO2-Ta2O5 / Ti electrode is used as the anode, the graphite sheet electrode is used as the cathode, and the electrolyte is preferably a 0.05 mol / L Na2SO4 aqueous solution; two electrodes used as the cathode and the anode are inserted into the electrolyte, and the PET microplastic powder obtained in step S1 is added to the electrolyte containing a surfactant, wherein the surfactant is selected from any one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, sodium dodecyl sulfonate, and sodium dodecylbenzene sulfonate, preferably sodium dodecyl sulfate (SDS), and the mass concentration of SDS is 0 mg / L to 100 mg / L, and the particle size of the PET microplastic powder is 145 mesh to 155 mesh, preferably 150 mesh; the pH of the electrolyte is adjusted to 4 to 7, and the electrolysis is stirred at a temperature of 80°C to 90°C, and the current density of the stirred electrolysis is controlled at 5 mA / cm 2 ~20mA / cm 2 , the electrolysis time is 2h to 12h, and the PET microplastics are degraded. In this step, the electrolysis is preferably stirred at a temperature of 85°C. After the electrolysis is completed, the undegraded PET microplastics are filtered with a 0.45μm filter membrane and dried. After drying, weigh and calculate the mass loss of the microplastics before and after electrolysis.
[0033] The degradation rate of PET microplastics is calculated according to formula (1):
[0034]
[0035] Where W0 represents the initial mass of the added PET microplastics, W t Indicates the mass of undegraded PET microplastics.
[0036] Example 1
[0037] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0038] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0039] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 10 mA / cm 2 , pH = 5, SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 6 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 68%.
[0040] like Figure 2 As shown, Figure 2 The following are scanning electron microscope photos of the PET microplastics in this example before and after electrochemical degradation, wherein (a) is a scanning electron microscope photo before electrochemical degradation, and (b) is a scanning electron microscope photo after electrochemical degradation. Figure 2 (a) shows that the surface of PET microplastics that have not been electrochemically degraded is rough and irregularly granular, with a particle size of about 75 μm; Figure 2 (b) shows that the PET microplastics that have undergone electrochemical degradation are still irregular particles, but the particle size is significantly reduced, some particles are broken, and a tightly stacked layered structure is formed on the surface of the particles. This may be due to the degradation of PET microplastics from the outside to the inside during the electrolysis process, and the amorphous part degrades faster and the crystalline area degrades slower.
[0041] Example 2
[0042] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0043] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0044] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 10 mA / cm 2, pH = 5, SDS concentration: 0 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 8 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 45%.
[0045] Example 3
[0046] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0047] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0048] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 10 mA / cm 2 , pH = 5, SDS concentration: 50 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 4 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 60%.
[0049] Example 4
[0050] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0051] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0052] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 10 mA / cm 2 , pH = 5, SDS concentration: 75 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 6 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 61%.
[0053] Example 5
[0054] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0055] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0056] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 10 mA / cm 2 , pH = 5, SDS concentration: 100 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 6 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 63%.
[0057] Example 6
[0058] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0059] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0060] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 5 mA / cm 2 , pH = 5, SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 4 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 45%.
[0061] Example 7
[0062] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0063] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0064] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 °C and the current density was 15 mA / cm 2 , pH = 5, SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 6 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 50%.
[0065] Example 8
[0066] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0067] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0068] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 20 mA / cm 2 , pH = 5, SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 6 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 47%.
[0069] Example 9
[0070] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0071] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0072] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 10 mA / cm 2 , pH = 4, SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 6 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 30%.
[0073] Example 10
[0074] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0075] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0076] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 10 mA / cm 2 , pH = 6, SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 6 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 55%.
[0077] Embodiment 11
[0078] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0079] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0080] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 10 mA / cm 2 , pH = 7, SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 6 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 48%.
[0081] Example 12
[0082] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0083] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0084] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 10 mA / cm 2 , pH = 5, SDS concentration: 25 mg / L, aeration flow rate: 0 mL / min, stirring electrolysis for 6 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 63%.
[0085] Example 13
[0086] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0087] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0088] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 10 mA / cm 2 , pH = 5, SDS concentration: 25 mg / L, aeration flow rate: 100 mL / min, stirring electrolysis for 6 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 65%.
[0089] Embodiment 14
[0090] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0091] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0092] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 10 mA / cm 2 , pH = 5, SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 2 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 35%.
[0093] Embodiment 15
[0094] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0095] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0096] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 10 mA / cm 2 , pH = 5, SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 4 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 48%.
[0097] Example 16
[0098] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0099] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0100] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 10 mA / cm 2 , pH = 5, SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 8 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 69%.
[0101] Embodiment 17
[0102] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0103] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0104] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 10 mA / cm 2, pH = 5, SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 10 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 70%.
[0105] Embodiment 18
[0106] This embodiment provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0107] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0108] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 °C and the current density was 10 mA / cm 2 , pH = 5, SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 12 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 69%.
[0109] Comparative Example 1
[0110] This comparative example is basically the same as Example 1, except that the electrolysis temperature in this comparative example is set to 25° C. That is, this comparative example provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0111] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0112] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 25 °C and the current density was 10 mA / cm 2 , pH = 5, SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 6 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 18%.
[0113] Comparative Example 2
[0114] This comparative example is basically the same as Example 1, except that the pH of the electrolyte in this comparative example is adjusted to 3. That is, this comparative example provides a method for degrading polyethylene terephthalate microplastics, comprising the following steps:
[0115] Pretreatment: Mix polyethylene terephthalate and water in a mass ratio of 1:20, place it in a polytetrafluoroethylene hydrothermal reactor and maintain it at 180°C for 12 hours, then cool it to 25°C, filter it and dry it to obtain PET microplastic powder.
[0116] Degradation of PET microplastics: The electrolysis experiment was carried out in a 500 mL reactor, with IrO2-Ta2O5 / Ti (10×5 cm) as the anode and a graphite sheet (9×5 cm) as the cathode. The electrodes were placed in parallel with a spacing of 4.5 cm. The electrolyte was a 0.05 mol / L Na2SO4 aqueous solution. 0.1 g PET powder (0.2 g / L, 150 mesh) was added. The electrolysis temperature was 85 ° C and the current density was 10 mA / cm 2 , pH = 3, SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min, stirring electrolysis for 6 hours. After the electrolysis, the undegraded PET microplastics were filtered with a 0.45 μm filter membrane and dried. After drying, weigh and calculate the mass loss of PET microplastics before and after electrolysis. The mass loss of PET microplastics before and after electrolysis was 15%.
[0117] The electrolysis experimental conditions of the above-mentioned Examples 1-18 and Comparative Examples 1-2 are shown in Table 1.
[0118] Table 1 Electrolysis experimental conditions of Examples 1-18 and Comparative Examples 1-2
[0119]
[0120]
[0121] like Figure 3 As shown, Figure 3 It is the weight loss rate of the electrochemical degradation of PET microplastics at different times in Example 1 and Examples 14-18. Figure 3 The results showed that the weight loss rate of PET microplastics did not increase significantly when the electrolysis time was extended after 6 hours of electrolysis.
[0122] Based on the above examples 1-18 and comparative examples 1-2, it can be seen that the optimal conditions for electrolysis are electrolysis temperature: 85°C; current density: 10 mA / cm 2 ; pH: 5; SDS concentration: 25 mg / L, aeration flow rate: 80 mL / min. Under these conditions, the degradation weight loss of PET microplastics can reach 68% after 6 hours of electrolysis.
[0123] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for degrading polyethylene terephthalate microplastics, characterized in that: The steps include: S1, pre-treating polyethylene terephthalate to obtain PET microplastic powder; S2, adding the PET microplastic powder obtained in step S1 to an electrolyte containing a surfactant, adjusting the pH of the electrolyte to 4-7, stirring and electrolyzing at a temperature of 80° C. to 90° C. to degrade the PET microplastic.
2. A method for degrading polyethylene terephthalate microplastics according to claim 1, characterized in that: The specific steps of the pretreatment are: mix polyethylene terephthalate and water in a mass ratio of 1:15 to 1:25, place it in a hydrothermal reactor and maintain it at 170°C to 190°C for 11h to 13h, then cool it to 20°C to 30°C, filter it and dry it to obtain PET microplastic powder.
3. A method for degrading polyethylene terephthalate microplastics according to claim 2, characterized in that: The mass ratio of polyethylene terephthalate to water is 1:
20. After mixing, the mixture is placed in a hydrothermal reactor and maintained at 180°C.
4. A method for degrading polyethylene terephthalate microplastics according to claim 1, characterized in that: The specific steps of electrolysis are: using IrO2-Ta2O5 / Ti electrode as anode and graphite sheet electrode as cathode, inserting the two electrodes used as cathode and anode respectively into the electrolyte, adding surfactant and PET microplastic powder obtained in step S1 into the electrolyte, and then stirring electrolysis to degrade PET microplastics. After the electrolysis is completed, the undegraded PET microplastics are filtered out with a 0.45μm filter membrane and dried.
5. The method for degrading polyethylene terephthalate microplastics according to claim 1, characterized in that: In step S2, aeration treatment is performed while stirring the electrolysis.
6. The method for degrading polyethylene terephthalate microplastics according to claim 1, characterized in that: During the stirring electrolysis process in step S2, the current density was controlled at 5 mA / cm 2 ~20mA / cm 2 ; The electrolysis time is 2h~12h; The aeration flow rate is 0mL / min~100mL / min.
7. A method for degrading polyethylene terephthalate microplastics according to claim 1, characterized in that: The electrolyte is a 0.01-0.1 mol / L Na2SO4 aqueous solution.
8. The method for degrading polyethylene terephthalate microplastics according to claim 1, characterized in that: The surfactant is selected from any one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate.
9. A method for degrading polyethylene terephthalate microplastics according to claim 8, characterized in that: The mass concentration of the surfactant is 0 mg / L to 100 mg / L.
10. The method for degrading polyethylene terephthalate microplastics according to claim 1, characterized in that: The particle size of the PET microplastic powder is 145 mesh to 155 mesh.
Citation Information
Patent Citations
Method for degrading bis-hydroxyethyl terephthalate
CN101250285A
Method for degrading polyethylene terephthalate
CN102153443A
Method for catalytically alcoholizing polyethylene terephthalate
CN102796002B
Method for degrading polyethylene glycol terephthalate (PET)
CN103641678A
A method for catalytic degradation of polyethylene terephthalate by polymetallic oxygen clusters
CN103951564B